2010
DOI: 10.1007/s12975-010-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation After Stroke: Mechanisms and Therapeutic Approaches

Abstract: Reperfusion of ischemic brain can reduce injury and improve outcome, but secondary injury due to inflammatory mechanisms limits the efficacy and time window of such treatments for stroke. This review summarizes the cellular and molecular basis of inflammation in ischemic injury as well as possible therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 175 publications
(178 reference statements)
2
60
0
Order By: Relevance
“…Furthermore, using a cell culture model of human BBB established with relatively late passage endothelial cells and astrocytes, in this study only one factor, i.e., glucose, out of many involved in ischemic damage could be manipulated, whereas a number of pro-inflammatory cytokines and circulating components during an ischemic stroke, notably tumor necrosis factor-a, interleukin-6, vascular endothelial growth factor, and thrombin, are known to affect BBB permeability. 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using a cell culture model of human BBB established with relatively late passage endothelial cells and astrocytes, in this study only one factor, i.e., glucose, out of many involved in ischemic damage could be manipulated, whereas a number of pro-inflammatory cytokines and circulating components during an ischemic stroke, notably tumor necrosis factor-a, interleukin-6, vascular endothelial growth factor, and thrombin, are known to affect BBB permeability. 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Inflammation takes part in the recovery after stroke and cerebral injury, but, simultaneously it is one of the threats which may worsen the stroke condition [35]. Inflammation during stroke is intermediated by both soluble factors, especially cytokines and also cellular components such as leukocytes and microglia, many of which have pro-inflammatory properties with promoting or destructive consequences [3,89]. ROS are generated as part of the natural immune response by inflammatory cells.…”
Section: Oxidative Stress-mediated Catastrophes Inflammationmentioning
confidence: 99%
“…Therefore, a significant hiatus exists during which no means of effective medical management is available for patients with AIS. Moreover, despite numerous clinical trials conducted to salvage cells from death, no significant breakthrough has been made to improve the outcome of stroke patients (5,6).…”
mentioning
confidence: 99%
“…Such cells, as infiltrate within the peri-infarcted areas of brain tissues from AIS patients (9, 10), become intimately involved in all stages of the ischemic cascade (7,8). Studies in experimental stroke have indicated that all these cells contribute to the death of ischemic neurons by promoting focal inflammatory reactions, direct killing, triggering of antigen-specific immune responses, or alterations in neuronal excitability (6,(10)(11)(12).…”
mentioning
confidence: 99%